Study on Synthesis and Photocatalytic Activity of Porous Titania Nanotubes - Huang Liu; Yanhua Zhang; Hongtao Yang; Wei Xiao; Lanlan Sun (Advances in Materials Science and Engineering)
Using the common natural cellulose substance (filter paper) and triblock copolymer (Pluronic P123) micelles as dual templates, porous titania nanotubes with enhanced photocatalytic activity have been successfully synthesized through sol-gel methods. Firstly, P123 micelles were adsorbed onto the surfaces of cellulose nanofibers of filter paper, followed by hydrolysis and condensation of tetrabutyl titanate around these micelles to form titania layer. After calcination to remove the organic templates, hierarchical titania nanotubes with pores in the walls were obtained. The sample was characterized by X-ray diffraction pattern (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption/desorption, Fourier Transform Infrared Spectroscopy (FT-IR), Ultraviolet-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS), and X-ray photoelectron spectroscopy (XPS). As compared with commercial P25 catalyst, the porous titania nanotubes prepared by this method displayed significantly enhanced photocatalytic activity for degrading methyl orange under UV irradiation. Within 10 minutes, the porous titania nanotubes are able to degrade over 70% of the original MO, while the value for the commercial Degussa P25 is only about 33%.